Performance of pneumatic and mechanical seeder-fertilizer at different speeds in soybean (Research, Society and Development, 2020)
Sowing is an operation that interferes with the development of soybean plants and, consequently, yield crop, which both seed distribution mechanisms and sowing speed can impair the success of the crop. In this context, the objective of this study was to evaluate the interference of mechanical and pneumatic distribution of seeds at different speeds both in the development and in yield of soybean in Oxisol. The study was developed using a randomized block design, in a 2 x 3 factorial scheme, with two seed distribution systems and three sowing speeds, with four replications, totaling 24 experimental units. In the first factor, seed distribution dosing systems (mechanical and pneumatic seeder, with negative vacuum) were used. In the second, there were different operating speeds (4, 8 and 12 km h-1). During the crop cycle, longitudinal distribution of plants, height and diameter of the collection were evaluated, and after harvest, mass of one thousand grains and crop yield. It was obtained larger number of plants, higher thousand seed weight and increased plant height in the pneumatic mechanism soybean seed distribution in the Midwest region Prudentópolis-PR. The speed of 4 and 8 km h-1 are more suitable for sowing soybeans for both mechanical and pneumatic seeders. The sowing mechanism, mechanical or pneumatic, does not affect the productivity of soybeans, when the edaphoclimatic conditions are adequate for the development of the crop. When considering the conditions of the Prudentópolis-PR region, with rains well distributed throughout the period of conduction of soybean crop, both systems of seed distribution are indicated, being appropriate to use sowing speed between 4 and 8 km h-1.